Characteristics of heat transfer and fluid flow in microtube and microchannel using conventional fluids and nanofluids: A review - Salman B.H.; Mohammed H.A.; Munisamy K.M.; Kherbeet A.Sh. (Elsevier Ltd, 2023)
Research on convective heat transfer on internal microtube and microchannel has been extensively conducted in the past decade. This review summarizes numerous researches on two topics; the first section focuses on studying the fluid flow and heat transfer behavior of different types of microtubes (MT) and microchannel (MC) at different orientations. The second section concentrates on nanofluids; its preparation, properties, behavior, and many others. The purpose of this article is to get a clear view and detailed summary of the influence of several parameters such as the geometrical specifications, boundary conditions, and type of fluids. The maximum Nusselt number is the main target of such research where correlation equations were developed in experimental and numerical studies are reported. The heat transfer enhancement of nanofluids along with the nanofluids preparation technique, types and shapes of nanoparticles, base fluids and additives, transport mechanisms, and stability of the suspension are also discussed. 2013 Elsevier Ltd. All rights reserved.